Mycobacterium chelonei Breast Abscess Associated With Nipple Piercing - Mark D. Pearlman (Hindawi Limited, 1995)
Background: Breast abscesses are typically seen in the setting of complicated mastitis in lactating women. Abscesses resulting from foreign bodies are not commonly seen in the breast. Over the past few decades, body piercing has become increasingly common, yet the infectious morbidity resulting from it is not well recognized. A breast abscess associated with nipple piercing is described in this report.